P10 Clinical features and outcome of arrhythmias requiring dc cardioversion in south wales. (2nd March 2016) - Fortner, Rainer; Scheller, Marcia; Uzun, Orhan
Abstract : Introduction: DC cardioversion is perceived as a drastic intervention in childhood and causes great anxiety in many clinicians despite being part of paediatric life support training programs. A recent survey amongst paediatric trainees reported that 56% felt they were not confident in defibrillation. There is no detailed study looking at its use and technical-clinical issues encountered in day to day practice in children. We aimed at investigating the presenting features and clinical outcomes of children requiring DC cardioversion in South Wales. Methods: We reviewed all cases identified in the paediatric cardiology database at the University Hospital of Wales who had received DC cardioversion in the past 20 years. Both case notes and cardiology database documentation were searched for relevant information. Patients over 18 years at time of cardioversion were excluded. Results: 28 children were identified. 16 of the children were male, 12 female. Most children requiring cardioversion were under 1 year of age (61%). All but one child (96%) survived. In 18 children sinus rhythm was restored after 1 shock (64%), children presenting in VF required 3 or more shocks. 12 children presented to UHW or to one of five welsh DCH as an emergency. Six were admitted electively for DC cardioversion. Seven neonates were admitted to SCBU with an antenatal diagnosis of supraventricular tachycardia (SVT) and three to SCBU with no known antenatal diagnosis. Only seven children (25%) had known congenital heart disease before DC cardioversion was required, with Ebstein's anomaly being the most common diagnosis. Only two of these seven presented as an emergency. Further three children presenting with arrhythmias requiring cardioversion were later diagnosed with dilated cardiomyopathy. Five children were known to have WPW syndrome, one child had long QT syndrome. Cardiac function around the time of cardioversion was impaired in 17 children (61%). 6 (21%) children required cardioversion for ventricular tachycardia or fibrillation, 22 (79%) for SVT. 10 children (36%) were unwell for longer than 24 h prior to presentation, mostly with nonspecific symptoms of lethargy and poor feeding. 13 (46%) required emergency intubation at presentation. Only one child of this cohort was shocked out of hospital by paramedics. Conclusions: In 20 years only 12 children presented as emergencies to the A & E departments in South Wales required DC cardioversion. DC cardioversion is most effective in supraventricular tachycardia but more than one shock is needed in ventricular arrhythmias.